Experimental analysis of the thermal behavior of concrete - Zatir, Sara; Rahal, Nacer; Beghdad, Houda; Souici, Abdelaziz; Aouad, Halima; Benmahdi, Khaled (Vojnotehnički glasnik / Military Technical Courier, 2023)
Introduction/purpose: When concrete structural members are subjected to fire and then exposed to slow or rapid cooling, there are various changes affecting density, porosity, thermal damage, speed of sound propagation, modulus of elasticity, compressive strength, absorptivity, etc. The heavy use of concrete to build structures on the one hand and the problem of fires on the other require a deep understanding of the effect of fire on the structural behavior of concrete, especially after cooling. So far, the two cooling methods used to put out a possible fire have been water and free air. Our objective is to experimentally analyze the use of the extinguisher as the third method of cooling concrete exposed to high temperatures. Methods: To achieve our objective, a series of mechanical and physical tests waw carried out on specimens 40 mm in diameter and 40 mm in height, exposed to high temperatures of 200, 400, and 600 °C. These test samples were then subjected to three different cooling regimes, namely: free air, water immersion, and extinguisher use.Results: The results clearly show that the use of the extinguisher is more appropriate than the other two cooling methods, namely, natural cooling and immersion in water.Conclusion: The results from this experimental study could be of practical use when trying to extinguish a possible fire in a concrete structure.
Keywords: concrete; fire; experimental analysis; extinguish; water; free air